Explaining Economic Growth in China: Testing Sociological Tools for Validity - Alexander Kurakin (Экономическая социология, 2014)
Today it makes little sense to ask why social scholars would be interested in China’s economy insofar as the answer is obvious. The growth rate of the Chinese economy and the duration of its growth period are stunning. It is likely that in the near future China will outrun the US in terms of GDP and will become the largest economy in the world. Moreover, China has made huge progress in GDP per capita. But this is not the only reason to be interested in China. Notably, the communist party is still in power there, and by the standards of Western democracies, China remains an authoritarian state. Taken together, these characteristics form a paradox: How could communists produce such huge economic growth? The recent history of socialist countries seems to show that this is impossible. Although the Soviet Union sometimes demonstrated rapid growth, it could not sustain the pace in the long run. In the Chinese case, we face a more fundamental phenomenon than just the mobilization of a country to achieve vital objectives (usually with high costs)."Capitalism from Below: Markets and Institutional Change in China" by Victor Nee and Sonja Opper suggests the answer to this question.